Integrin-Adhesion Ligand Bond Formation of Preosteoblasts and Stem Cells in Three-Dimensional RGD Presenting Matrices - Hsiong, Susan X. (2008)
Cell-interactive polymers have been widely used as synthetic extracellular matrices to regulate cell function and promote tissue regeneration. However, there is a lack of quantitative understanding of the cell–material interface. In this study, integrin-adhesion ligand bond formation of preosteoblasts and D1 stem cells with RGD presenting alginate matrices were examined using FRET and flow cytometry. Bond number increased with adhesion ligand density but did not change with RGD island spacing for both cell types. Integrin expression varied with cell type and substrate in 2D culture, but the integrin expression profiles of both cell types were similar when cultured in 3D RGD presenting substrates and distinct from 2D culture. In summary, combining a FRET technique to quantify bond formation with flow cytometry to elucidate integrin expression can define specific cell–material interactions for a given material system and may be useful for informing biomaterial design strategies for cell-based therapies.